Recent Rapid Increase of Cover Crop Adoption Across the U.S. Midwest Detected by Fusing Multi‐Source Satellite Data. Issue 22 (15th November 2022) - Zhou, Qu; Guan, Kaiyu; Wang, Sheng; Jiang, Chongya; Huang, Yizhi; Peng, Bin; Chen, Zhangliang; Wang, Sibo; Hipple, James; Schaefer, Dan; Qin, Ziqi; Stroebel, Samuel; et al.
Abstract: Cover crops have critical significance for agroecosystem sustainability and have long been promoted in the U.S. Midwest. Knowledge of cover cropping variations and impacts of government policies remains very limited. We developed an accurate and cost‐effective approach utilizing satellite fusion data, environmental variables, and machine learning to quantify cover cropping in corn and soybean fields from 2000 to 2021 in the U.S. Midwest. We found that cover crop adoption in most counties was stagnant from 2000 to 2011, but has significantly increased from 2011 to 2021. The adoption of 2021 is four times that of 2011, which was highly correlated to the funding for conservation programs. However, the percentage of cover crop adoption in the U.S. Midwest is still low (7.2%). Our work fills a critical gap in quantifying long‐term field‐level cover crop adoption at large regions and highlights the potential importance of incentive programs to promote sustainable agricultural practices. Plain Language Summary: Cover crops typically grow after cash crop harvesting and before the following season's planting of cash crops, and can bring benefits to agricultural sustainability. To stimulate cover crop adoption in the U.S. Midwest, the U.S. government has made significant financial and technical support to farmers for cover cropping (e.g., USDA Environmental Quality Incentives Program invested over 14 billion in conservation practices from 2010 to 2020). However, large‐scale and long‐term cover cropping information in the U.S. Midwest is largely missing. Timely and cost‐effective monitoring and verification of cover crop adoption are urgently needed. We utilized multi‐source remote sensing data and large amounts of ground truth data to develop effective approaches to detect cover crop adoption from 2000 to 2021 in a cost‐effective manner. We found that cover cropping acreage has significantly increased four times from 2011 to 2021. We also found the increase in cover crop adoption is highly correlated to the funding from federal and state conservation programs. The incentive programs could play an important role in promoting sustainable agricultural practices. Key Points: We developed a scalable remote sensing framework to detect field‐level cover cropping in the U.S. Midwest from 2000 to 2021 Cover cropping adoption rate in the U.S. Midwest has significantly increased by four‐fold from 1.8% in 2011% to 7.2% in 2021 Cover cropping rate is highly correlated to the incentives of federal and state conservation programs